Online Psychological Testing System (OPTS) / Tan Kien Leong - Tan, Kien Leong (2002)
Online Psychological Testing System (OPTS) is an Internet-based system aim at provides a central place on the Internet to give information about the practice of psychology knowledge to the user. The system architecture for OPTS, which is developed in web-based can be divided into client (web browser), web server and database server. Before developing OPTS, researches have been done to understand various new concepts, which are relevant to this project. Among the topic are psychological questions, Internet, client/server concepts and other relevant topic. Questionnaire is used to get the feedback from the students in University of Malaya about their opinions with this project. Methodology used to develop this application is prototyping, where part of the system can construct quickly to understand and clarify the requirements and designs of the system. OPTS can be divided into 2 sections, which are the Student and Administrator. At the end of the project, OPTS will expect to have security checking for authorized user, develop database to keep all the records, create database maintenance and creation of interactive homepages to deploy information to students. OPTS is developed using Active Server Pages technologies on the Microsoft WindowsNT platform utilizing database created and stored from Microsoft Access 2000. It is believed that this web-based database system will gradually become an essential to everyone in the future.